Laurent polynomials, GKZ-hypergeometric systems and mixed Hodge modules - Reichelt, Thomas (Compositio mathematica, 2014)
We endow certain GKZ-hypergeometric systems with a natural structure of a mixed Hodge module, which is compatible with the mixed Hodge module structure on the Gauß-Manin system of an associated family of Laurent polynomials. As an application we show that the underlying perverse sheaf of a GKZ-system with rational parameter has quasi-unipotent local monodromy.
Gesehen am 14.08.2017